Analisis Nilai Religius dan Nilai Sosial pada Kumpulan Cerpen Panggilan Rasul Karya Hamsad Rangkuti serta Pemanfaatannya Sebagai Bahan Ajar di SMA - Damayanti, Noni (Jurnal Artikula, 2022)
ABSTRACT This study aims to identify and describe the religious and social values ​​contained in the collection of short stories "Call of the Apostles" by Hamsad Rangkuti and their use as teaching materials in high school. The research method used in this research is descriptive method. The data source used in this study is a collection of short stories called the Apostles' Call by Hamsad Rangkuti. The technique used in data collection uses reading and note-taking techniques. Based on the results of the study found religious values, namely the value of faith in God found as many as 2 data, the value of piety to Him 5 data, the value of repentance 1 data, the value of halal 1 data, the value of haram 1 data, the value of makruh 2 data, the value of permissible 1 data, the value of patient 1 data, humble value 2 data, tawakal value 2 data, honest value 3 data, sincere value 2 data, and discipline value 1 data. In the social value, the value of service was found as many as 5 data, the value of helping 2 data, the value of family 1 data, the value of loyalty 1 data, the value of caring 5 data, the value of having 2 data, the value of discipline 3 data, the value of empathy 1 data, the value of justice 1 data , and the value of cooperation 3 data. Keywords: Religious Values, Social Values, Collection of Short Stories